Evaluation of an anthropometric head surrogate exposed to chisel-nosed fragment simulating projectile impact - Pandey, Punit Kumar; Ganpule, S. G. (Frontiers in Mechanical Engineering, 2024)
Fragment-induced penetrating injuries pose a significant threat in modern combat. Explosions from explosive devices generate metallic fragments that can lethally penetrate various body regions, with the head being particularly most vulnerable to fatality in terms of penetration. Hence, understanding the head’s response to fragment impact is crucial. To this end, this study investigated the ballistic response of an anatomically accurate anthropometric head surrogate to fragment impact. The head surrogate comprised simulants for the three major layers of the head (skin, skull, and brain). Using a pneumatic gas gun, we impacted chisel-nosed fragment simulating projectiles (FSPs) of 1.10-g and 2.79-g on the head surrogate. We analyzed the ballistic response of the head surrogate in terms of ballistic limit velocities (V50), energy densities (E50/A), and failure mechanisms in each layer. The results indicated sensitivity to the FSP size. The 1.10-g FSP had a ∼41% higher V50 and a ∼63% higher E50/A compared to the 2.79-g FSP. Additionally, each head surrogate layer exhibited distinct failure mechanisms. The skin simulant failed due to a combination of shearing and elastic hole enlargement, forming a cavity smaller than the size of the FSP. The skull simulant fractured, creating a cavity at the entry point matching the FSP size. The brain simulant failure involved shearing of the cavity and penetration of fractured skull fragments. We also observed no significant difference in response when introducing a flexible neck attachment on which the head surrogate was mounted. Furthermore, comparisons of an anthropometric (close-shape) head surrogate with a simplified open-shaped head surrogate revealed the minimal influence of the head curvature on the response due to the localized nature of fragment penetration. These findings provide a comprehensive understanding of the head surrogate’s mechanical response to fragment impact. The insights from this work hold significant value in the assessment of penetrating head injury, especially against small fragments. The results can be applied in modern warhead design and forensic investigations.